Legal Policy of Green Investment: A Study of the Green Constitution and Fiqh Bi’ah towards Net Zero Emissions in Indonesia - Lutfi, Mustafa; Supriyadi, Aditya Prastian; Nur, Asrul Ibrahim; Bahagiati, Kurniasih; Ramadhita, Ramadhita (Universitas Negeri Semarang, 2025)
There is an urgent need for a legal policy of green investment law to reduce gas emissions in Indonesia based on the perspective of the green constitution and Fiqh Bi'ah in the contemporary era. This urgency is parallel to the development of the global response to sustainable economic transformation to achieve net zero emissions by 2060. However, the green investment policy design has to hold a strategic position in Indonesia's positive law because it always remains partial. In other words, such a policy requires comprehensive examination based on the Green Constitution and Fiqh Bi'ah in constructing future national, legal, and political designs relevant to the net zero emission paradigm. This study employs a normative legal research method with philosophical, conceptual, historical, comparative, and statutory approaches. Primary, secondary, and tertiary legal sources were analysed using a qualitative juridical method. The findings indicate that the 1945 Constitution has constitutionally accommodated the principles of the Green Constitution, which align with Fiqh Bi’ah regarding sustainable environmental management as mandated by the Quran. This legal construction can be a strategic foundation for green investment policies based on net zero emissions to address climate change. The alignment between the Green Constitution and Fiqh Bi’ah strengthens green investment policies as a concrete step toward preserving the earth for the sustainability of future generations. Thus, integrating these two perspectives becomes a primary element in building a sustainable civilisation oriented towards environmental preservation.